Fabrication of a Robust PEM Water Electrolyzer Based on Non‐Noble Metal Cathode Catalyst: [Mo3S13]2− Clusters Anchored to N‐Doped Carbon Nanotubes. Issue 37 (16th August 2020) - Holzapfel, Peter K. R.; Bühler, Melanie; Escalera‐López, Daniel; Bierling, Markus; Speck, Florian D.; Mayrhofer, Karl J. J.; Cherevko, Serhiy; Pham, Chuyen V.; Thiele, Simon
Abstract: High investment costs and a dependence on noble metal catalysts currently obstruct the large‐scale implementation of proton exchange membrane water electrolyzers (PEMWEs) for converting fluctuating green electricity into chemical energy via water splitting. In this context, this work presents a high‐performing and stable non‐noble metal catalyst for the hydrogen evolution reaction (HER), consisting of [Mo3 S13 ] 2− clusters supported on nitrogen doped carbon nanotubes (NCNTs). Strikingly, a significant electrochemically induced activation of the Mo3 S13 ‐NCNT catalyst at high current densities is observed in full cell configuration, enabling a remarkable current density of 4 A cm −2 at a cell voltage of 2.36 V. To the authors' knowledge, this is the highest reported value to date for a PEMWE full cell using a non‐noble metal HER catalyst. Furthermore, only a minor degradation of 83 µV h −1 is observed during a stability test of 100 h constant current at 1 A cm −2, with a nearly unchanged polarization behavior after the current hold. Catalyst stability and activity are additionally analyzed via online dissolution measurements. X‐ray photoelectron spectroscopy examination of the catalyst before and after electrochemical application reveals a correlation between the electrochemical activation occurring via electrodissolution with changes in the molecular structure of the Mo3 S13 ‐NCNT catalyst. Abstract : A remarkable current density of 4 A cm −2 at 2.36 V and minor degradation during 100 h current hold at 1 A cm −2 are demonstrated for a proton exchange membrane water electrolyzer using [Mo3 S13 ] 2− clusters supported on nitrogen doped carbon nanotubes as a hydrogen evolution reaction catalyst. This work also reveals insights into the activation behavior of this catalyst group.